2021
DOI: 10.3390/s21030826
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Source Localization in Wastewater Networks

Abstract: In December 2016, the wastewater treatment plant of Baarle-Nassau, Netherlands, failed. The failure was caused by the illegal disposal of high volumes of acidic waste into the sewer network. Repairs cost between 80,000 and 100,000 EUR. A continuous monitoring system of a utility network such as this one would help to determine the causes of such pollution and could mitigate or reduce the impact of these kinds of events in the future. We have designed and tested a data fusion system that transforms the time-ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 42 publications
(43 reference statements)
1
20
0
Order By: Relevance
“…We propose an enhanced data fusion algorithm for the detection, localization, and quantification of pollutants in WWNs. This article extends the system depicted in Chachuła et al [ 24 ], where we proposed the preliminary and very limited version of the data fusion algorithm. The algorithm presented in Chachuła et al [ 24 ] represents the sewage network as a directed tree.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…We propose an enhanced data fusion algorithm for the detection, localization, and quantification of pollutants in WWNs. This article extends the system depicted in Chachuła et al [ 24 ], where we proposed the preliminary and very limited version of the data fusion algorithm. The algorithm presented in Chachuła et al [ 24 ] represents the sewage network as a directed tree.…”
Section: Introductionmentioning
confidence: 63%
“…This article extends the system depicted in Chachuła et al [ 24 ], where we proposed the preliminary and very limited version of the data fusion algorithm. The algorithm presented in Chachuła et al [ 24 ] represents the sewage network as a directed tree. In this structure, there is one and only one path from any point of the sewage network to sink.…”
Section: Introductionmentioning
confidence: 63%
“…In addition, it will be further evaluated with larger sewage networks, more substances, and different sewage hydraulic conditions in further publications. A benchmark of different localization methods–such those described in [ 24 , 27 , 28 , 29 , 30 ]—for an estimation of the pollution source could be considered as an important step forward in this area, as well as adapting effective existing methods for detection of polluting sources in similar environments, such as in [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chachula et al [ 29 ] proposed a data fusion algorithm for solving the pollution source localization problem in wastewater networks. The approach does not utilize machine learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Chachula et al [ 36 ] implemented and evaluated a data fusion system that transforms the time-series of sensor measurements into a collection of source-localized discharge events. Based on experiment results, the authors have shown that the proposed framework is an efficient solution for pollution source localization because it can narrow down the number of sources of pollution nodes and therefore achieved faster sensor observations processing (i.e., 100 observations per second).…”
Section: Related Workmentioning
confidence: 99%